2018
DOI: 10.1002/ptr.6253
|View full text |Cite
|
Sign up to set email alerts
|

Gossypin inhibits gastric cancer growth by direct targeting of AURKA and RSK2

Abstract: Gossypin is a flavone extracted from Hibiscus vitifolius, which has been reported to exhibit anti‐inflammatory, antioxidant, and anticancer activities. However, the anticancer properties of gossypin and its molecular mechanism of action against gastric cancer have not been fully investigated. In the present study, we report that gossypin is an Aurora kinase A (AURKA) and RSK2 inhibitor that suppresses gastric cancer growth. Gossypin attenuated anchorage‐dependent and anchorage‐independent gastric cancer cell g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
0
18
0
5
Order By: Relevance
“…AURKA is overexpressed in a variety of human cancers, including gastric cancer, breast cancer, bladder cancer, head and neck squamous cell carcinoma and HCC [39][40][41]. And it plays an important role in the mitotic cell cycle by participating in centrosome replication, isolation and maturation [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…AURKA is overexpressed in a variety of human cancers, including gastric cancer, breast cancer, bladder cancer, head and neck squamous cell carcinoma and HCC [39][40][41]. And it plays an important role in the mitotic cell cycle by participating in centrosome replication, isolation and maturation [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoid could protect human sperm against the damaging effects of FeSO 4 /H 2 O 2 (Huang et al 2014). Recently, it has been found that flavone works against cancer growth by direct targeting (Ganai 2017;Sajjadi et al 2018;Wang et al 2018b), and inhibits migration through DLC1/RhoA pathway by decreasing ROS generation in cancer cells (Zhu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Lapachol is a 1,4‐naphthoquinone compound (Figure a). Previously, JB6 mouse epithelial cells have been used to identify potential molecular targets of selected compounds, and MAPK and AKT signaling are strongly activated by epidermal growth factor (EGF) stimulation (Wang et al, ). Therefore, to identify potential molecular targets of lapachol, we first investigated whether lapachol could affect EGF‐induced various signaling molecules in JB6 mouse epithelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we suggest that lapachol can inhibit the activity of RSK2 and lead to reduced expression of cell cycle marker proteins. Additionally, inhibition of phosphorylated RSK could induce apoptosis by upregulating the expression levels of cleaved caspases, PARP, and cytochrome c (Wang et al, ). Therefore, we next investigated whether lapachol could induce apoptosis of ESCC cells.…”
Section: Discussionmentioning
confidence: 99%